The first record of European roller Coracias garrulus Linnaeus, 1758 for Nepal - Gurung, Ram Bahadur; Baral, Rishi (Nepalese Journal of Zoology, 2022)
European roller Coracias garrulus was recorded and photographed for the first time in Nepal on 29 August 2021 at Kekighan, Lomanthang Rural Municipality Ward Number-5, Upper Mustang (29° 10.779’ N, 83° 58.218’E) at an elevation of 3781 m in the Annapurna Conservation Area by the first author who considered it was an immature bird. Later, a photograph of the bird was used for confirmation of its identification.